Sustainable development goals through the lens of local churches: An interdisciplinary study - Mawethu Msebi; Jacques W. Beukes (Verbum et Ecclesia)
This article reports on the findings of the local churches’ involvement in the Sustainable Development Goals (SDGs) in Tembisa in Gauteng province of South Africa. The article employed Richard Osmer’s model of the four tasks of practical theological interpretation, focussing on narrating and examining the situation in the Tembisa community. The article relied on documentary analysis and in-depth semi-structured interviews. The study findings revealed that local churches could significantly promote the SDGs within their local communities. The study identified essential factors such as human rights, gender equality, peace and justice, and biodiversity conservation as crucial for achieving developmental outcomes. The challenges that local churches face in implementing the SDGs were also discussed.